Community-Based Health Education and Personal Hygiene Knowledge Among Hypertensive Older Adults: A Gerontologic Nursing Perspective - Dwi Widyastuti; Deby Krisna Yuwanda; Milkhatun Milkhatun (Yayasan Ahmad Mansyur Nasirah, 2026)
Hypertension is a major global health problem with increasing prevalence among older adults and requires comprehensive management beyond pharmacological treatment. From a gerontic nursing perspective, strengthening self-care, including personal hygiene, is essential to prevent complications and improve health outcomes. However, age-related cognitive and sensory changes often reduce the effectiveness of conventional health education. This study aimed to evaluate the effectiveness of a community-based educational video in improving personal hygiene knowledge among older adults with hypertension. A quantitative pre-experimental study using a one-group pretest–posttest design was conducted among 38 adults aged ≥60 years recruited through purposive sampling at a public health center in Samarinda, East Kalimantan, Indonesia. Knowledge was assessed using a validated and reliable structured questionnaire before and after participants viewed a seven-minute educational video developed according to gerontic nursing principles. Data were analyzed using descriptive statistics and the Wilcoxon Signed Rank Test. Personal hygiene knowledge improved significantly following the intervention. Before the intervention, most participants had good or moderate knowledge, whereas after the intervention all participants achieved a good level of knowledge, with a statistically significant improvement (p < 0.001). These findings demonstrate that community-based educational videos are an effective, practical, and age-appropriate strategy for improving personal hygiene knowledge among older adults with hypertension and support their integration into promotive and preventive gerontic nursing services in primary health care and community settings.